WANITA PERAJIN TENUN TRADISIONAL DI NAGARI HALABAN, KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA, SUMATERA BARAT - Hendrawati .; Ermayanti . (Universitas Andalas, 2016)
Article based on field research in Halaban Village, Lareh Sago Halaban Subdistrict, Lima Puluh Kota District. This village is one of center of weaving traditional craft in West Sumatra, beside that Pandai Sikek and Silungkang, which is the most women activity in this village. The aim of research is described of daily life, work as handicrafts workers woven traditional .The research found that women in this village has two role, besides the housewives, they also breadwinner second after her husband, economically a woman has a high position and an important role in household . This activity very need to overcome in the economy household.